Fluorinated oxysterol analogues: Synthesis, molecular modelling and LXRβ activity - Rodriguez, Cristian Ramon (2017)
Liver X receptors (LXRs) are nuclear receptors that play central roles in the transcriptional control of lipid metabolism. The ability of LXRs to integrate metabolic and inflammation signalling makes them attractive targets for intervention in human metabolic diseases. Several oxidized metabolites of cholesterol (oxysterols) are endogenous LXR ligands, that modulate their transcriptional responses. While 25R-cholestenoic acid is an agonist of the LXRs, the synthetic analogue 27-norcholestenoic acid that lacks the 25-methyl is an inverse agonist. This change in the activity profile is triggered by a disruption of a key interaction between residues His435 and Trp457 that destabilizes the H11-H12 region of the receptor and favors the binding of corepressors. The introduction of fluorine atoms on the oxysterol side chain can favor both hydrophobic interactions as well as hydrogen bonds with the fluorine atoms and may thus induce changes in the receptor that may lead to changes in the activity profile. To evaluate these effects we have synthesized two fluorinated 27-nor-steroids, analogues of 27-norcholestenoic acid, the 25,25-difluoroacid and the corresponding 26-alcohol. The key step was a Reformatsky reaction on the C-24 cholenaldehyde, with ethyl bromodifluoroacetate under high intensity ultrasound (HIU) irradiation, followed by a Barton-McCombie type deoxygenation. Activity was evaluated in a luciferase reporter assay in the human HEK293 T cells co-transfected with full length human LXRβ expression vector. The 25,25-difluoro-27-norcholestenoic acid was an inverse agonist and antagonist similar to its non-fluorinated analogue while its reduced derivative 25,25-difluoro-27-norcholest-5-ene-3β,26-diol was an agonist. Molecular dynamics simulation of the ligand-receptor complexes showed that the difluoroacid disrupted the His435-Trp457 interaction although the resulting conformational changes were different from those induced by the non-fluorinated analogue. In the case of the difluoroalcohol, the fluorine atoms actively participated in the interaction with several residues in the ligand binding pocket leading to a stabilization of the active receptor conformation.